Konflik Batin Tokoh Utama dalam Novel Namaku Alam Karya Leila S. Chudori - Husna, Jazaanil; Kasnadi, Kasnadi; Ismail, Ahmad Nur (LEKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The novel Namaku Alam by Leila S. Chudori is a literary work that contains various life problems that often occur in the general public. One of them is the inner conflict depicted by the author through the main character, namely Segara Alam. The various conflicts experienced by the characters certainly have factors that cause the inner conflict to arise in the character. This study aims to describe the factors that cause the inner conflict of the Alam character in the novel Namaku Alam. This research was conducted using a qualitative descriptive method. And analyzed using a qualitative literature review approach. The study and analysis in this study focused on the study of personality psychology, specifically the inner conflict contained in the object of research, namely the novel My Name is Alam. The study of the inner conflict of the main character uses a literary psychology approach using Abraham Harold Maslow's Humanistic Theory known as Maslow's Hierarchy of Needs. The results of this study indicate that the novel Namaku Alam by Leila S. Chudori contains several inner conflicts experienced by the Alam character. so that it can be identified that there are five factors that cause inner conflict in Alam to appear, namely: (1) unfulfilled physiological needs, (2) unfulfilled security needs, (3) unfulfilled love, affection, and belonging needs, (4) unfulfilled appreciation needs, and (5) unfulfilled self-actualization needs.